Long-term optical stimulation of channelrhodopsin-expressing neurons to study network plasticity - Lignani, Gabriele; Ferrea, Enrico; Difato, Francesco; Amaru`, Jessica; Ferroni, Eleonora; Lugara`, Eleonora; Espinoza, Stefano; Gainetdinov, Raul R.; Baldelli, Pietro; Benfenati, Fabio (Frontiers in Molecular Neuroscience, 2013)
Neuronal plasticity produces changes in excitability, synaptic transmission, and network architecture in response to external stimuli. Network adaptation to environmental conditions takes place in time scales ranging from few seconds to days, and modulates the entire network dynamics. To study the network response to defined long-term experimental protocols, we setup a system that combines optical and electrophysiological tools embedded in a cell incubator. Primary hippocampal neurons transduced with lentiviruses expressing channelrhodopsin-2/H134R were subjected to various photostimulation protocols in a time window in the order of days. To monitor the effects of light-induced gating of network activity, stimulated transduced neurons were simultaneously recorded using multi-electrode arrays. The developed experimental model allows discerning short-term, long-lasting and adaptive plasticity responses of the same neuronal network to distinct stimulation frequencies applied over different temporal windows.